Endoperio Lesion: An Overview - Sumit Dash1 , Debkant Jena1, Siba Jena2 , Swapna Kumari3 , Narottam Praharaj3 , Manali Nath4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The most common problems associated with tooth pain were endoperio lesions. It was very difficult todiagnose endoperio lesions by clinical or simply intra oral peri-apical radiograph. 50 % of tooth mortalityrates are responsible for the endoperio lesion, the correct diagnosis was needed for appropriate treatmentplanning. This paper review the current diagnostic tools and treatment planning of endoperio lesion toachieve the best outcome.